Three-Dimensional Printers and Their Application in Dental Prostheses - Seyed Shojaedin Shayegh; Seyed Mohammad Reza Hakimaneh; Hedie Derakhshi (Mashhad University of Medical Sciences, 2022)
Introduction: Three-dimensional (3D) printing is a layer-by-layer fabrication method used to manufacture 3D models of complex structures. This technology has multiple methods, materials, and equipment. The present study aimed to investigate the use of 3D printers in manufacturing dental prostheses, various processing methods, materials, and the accuracy of each.Materials and Methods: A standard search method was used in PubMed and Google scholar databases. The inclusion criterion was articles published in English in the field of manufacturing dental prostheses by additive methods between 2015 and 2020.Results: A total of 2,250 articles were retrieved from databases, using the keywords "3D printing" OR "Additive manufacturing" OR "Rapid prototyping" AND "Dental prostheses" OR "Dental Prosthetics" OR "Digital dentistry".According to the exclusion criteria, 27 articles (3 review, 2 in vivo, and 22 in vitro studies) related to 3D printing technology in prostheses were selected. 3D. In dentistry, stereolithography (SLA), Selective Laser Melting (SLM), Fused Deposition Modeling (FDM), and Material jetting (inkjet) have been so far used to make surgical guides, implants, casts, special trays, removable prostheses, casting patterns, metal frameworks, and fixed prostheses.Conclusion: The advent of 3D and digital technology has had a significant impact on the reconstruction of teeth and prosthetic works. The quality of prostheses made by this technology is clinically acceptable; therefore, they can replace conventional methods. The printing methods and materials used in dentistry are improving every day, and for the successful application of this technique, we need a complete and up-to-date familiarity with the method of using the materials, limitations, and benefits of this new technique.